Drivers of water-system vulnerabilities in fragile and conflict-affected communities in Adamawa State, Nigeria - Onyeneke, R.; Okem, Andrew; Osei-Amponsah, Charity (International Water Management Institute, 2024)
Water security in Adamawa State in northeastern Nigeria is influenced by socio-economic disparities as well as armed and non-armed conflicts. The challenge is compounded by the impacts of climate change. Using data from a survey of 400 households across 20 communities in 10 Local Government Areas (LGAs), comprising community members and internally displaced persons (IDPs), the study examined adaptive capacity, sensitivity, and exposure to water-related risks regarding household consumption and agricultural livelihoods. The results revealed that LGAs such as Girei and Yola South possess higher adaptive capacities, reducing their vulnerability, while Song and Hong are more vulnerable due to lower adaptive capacities and higher sensitivity and exposure to environmental and conflict-related risks. Socio-economic characteristics of the IDP households indicated substantial variability in education, income, and healthcare access—further influencing vulnerability levels. This analysis underscores the need for targeted policy interventions that enhance community resilience, focusing on improving adaptive capacities, reducing sensitivities, and effectively managing exposure to water-related conflicts.